DOWÓD Z OPINII RODZINNEGO OŚRODKA DIAGNOSTYCZNO-KONSULTACYJNEGO W SPRAWACH O ROZWÓD I JEGO WPŁYW NA TREŚĆ WYROKU W ŚWIETLE WYNIKÓW BADAŃ AKTOWYCH - Stojanowska, Wanda (Zeszyty Prawnicze, 2017)
THE OPINION OF THE FAMILY DIAGNOSTIC-ADVISORY CENTRE AS THE EVIDENCE IN DIVORCE CASES AND ITS INFLUENCE ON JUDGEMENTS (IN THE LIGHT OF C OURT RECORDS) Summary The present article contains results of studies conducted in the Institute of Justice in Warsaw. Basis for the research was 100 judgments in divorce cases by Polish provincial courts from 1997 to 1998. Each of the examined judgments was done after hearing by court of the Family Diagnostic - Advisory Centre (FDAC) opinion in cases including decision as to the guilt for breaking up of marriage and subsequent granting of the paternal authority to the innocent party. The study is going to establish relation between opinions by the FDAC and judgments. The study contains complex and detailed analysis of court decision and its grounds. It shows that opinion given by FDAC is very influential for courts granting judgments which followed it in 80% of analyzed cases. However not all of the suggestions given by experts were relevant. In the majority of the examined cases a mistake made by the expert consisted of the ignorance of law and consequendy of the ambiguous wording of the opinion. Such an opinion was then followed by the judge who usually chose the simplest solution granting the full parental authority to both of the divorced spouses thus avoiding the time consuming and laborious procedure based on the article 58 of the Code of Family and Guardianship Law determining possibility of limitation of the parental authority. Such approach could be declared as an opportunistic one, and provokes postulate de lege ferenda for abolishment of the institution of granting the full parental authority to both of the divorced spouses. Proposed change should simplify courts procedure as well as enable the FDEC to develop its activity as family advisory centers which until now does not exist in Polish legal system.